Impact of a person-centered bowel program on the frequency of nights with bowel movement in dependent elderly people in nursing home: A single-centre randomized controlled trial. (November 2022) - Seigneurin-Hérissé, Pascale; Toniolo, Jean; Marchat, Noëmie; Micallef, Ludovic; Labrunie, Anaïs; Delaide, Valérie; Beloni, Pascale
Abstract: Introduction: Bowel movements and sleep disturbances in the elderly impact their quality of life and dignity. The management of bowel movements is one of carers' main activities in nursing homes. This activity is under-recognized. It is routinely managed with laxatives or anti-diarrhea treatments, rather than being targeted at each resident's habits. We hypothesized that the implementation of a daytime person-centered bowel program in dependent elderly nursing-home residents could reduce nocturnal bowel movements and sleep disturbance due to night-time care activities. Our study evaluated the impact of a bowel program on the frequency of nights with bowel movement. Method: We conducted a single-center randomized controlled trial in two parallel groups: a control group with usual management versus an experimental group with the implementation of the person-centered bowel program. Results: Fifty dependent elderly residents of nursing homes for over one month were included. The implementation of the person-centered bowel program significantly impacted the frequency of nights with bowel movement: 12.0 (7.0; 15.5) in the control group versus 3.7 (2.0; 6.0) in the experimental group (p < 0.000). The strategy had no significant impact on laxative intake (p = 0.470). Conclusions: The introduction of a daytime person-centered bowel program significantly reduces the frequency of nights with bowel movements for dependent nursing-home residents. This person-centered strategy restores a key role to this basic need care. Further studies could explore the impact of this program on respect, dignity, comfort and night-time rest. It also offers carers new perspectives on care, with respect to the human being. Study registration: The study was registered in ClinicalTrials N°NCT03118401. Tweetable abstract: A daytime bowel program significantly reduces the number of nights with bowel movements for dependent nursing-home residents.